(3Gdbhd GdhGVM GdCTgQ aj Mce GdeYGedI HGdYTQI CMO YTQs - (3YHjO Gddg Hf eMeO Hf bWfIs ((3QVhGf Hf CMeO Hf YHO GdQMef HGQVhGf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQY GdCMcGe CeG HYO agPg fHPg dWjaI JJYdb HHjGf Mce GdeYGedGJ GdLGQjI Hjf GdfGS ai gPg GdCRefI , ef JYGWI GdQHG hGdJejd dPdc HCfhGY GdMjd hSejJgG HGdbhd GdhGVM s
(3BNQgG (B:s
(3hZPG bO aQZfG ef GdebUhO hCJjfG Ydjg , adfYWa HjGf GdSHH GdMGed Ydi JCdja Pdc afbhd bGd Pdc hLeYg YHOhf Hf eMeO Hf YhV Hf bWfg , JLGhR Gddg Yfg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B54 - (3U(B74s
(3HgG fXGe GdJYbjHIs
(3YdjgG JbjjOGJs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs